Service Quality Management: the search for a differential by small companies in the supermarket sector in the northwest of the state of São Paulo. - Tofoli, Eduardo Teraoka (Revista Gestão da Produção Operações e Sistemas, 2007)
In such a competitive market, to be active is a fundamental factor for the company. It is xx necessary to give theconsumer greater attention and mainly to the general factors of the company. The total quality is a factor thatdifferentiates the companies in the market and its habitual practice, focused on the important element, that is,the consumer. It is necessary that the entrepreneur uses his/her tools on behalf of the consumers, both internaland external. It is essential to plan actions with the eyes turned to the changes that happen in the market. Thedifferential lies on those who desire it and seek for it as an ally. In this sense, a field research was accomplishedwith xx small supermarkets xx xx from northwest of São Paulo state, with the objective of verifying the importanceof the quality in services for the xx supermarkets in their everyday management aiming at verifying if thequality in service xx helps the company to improve its participation in the market. Those data were analyzedwith SPSS software and it was demonstrated that the company, which is concerned with the quality has a goodperformance in the market.Key-Words: Total quality; Services; Supermarkets